Overcoming Invisible Barriers: How Coaching Brings New Mothers Back to the Social and Entrepreneurial Stage - Zahra Ghiafeh Davoudi; Ehsan Chitsaz; Maryam Seyfikar Qomi (زن در توسعه و سیاست)
The economic and social development of society is significantly influenced by the contributions of women. Their presence not only enhances the financial status of families but also promotes diversity and innovation in the labor market and society. However, numerous obstacles arise for mothers with children under the age of three when they attempt to resume their professional and social responsibilities. The current study investigates the influence of the “Trust Yourself” coaching approach on the social engagement and entrepreneurship of mothers. Two groups were utilized in this quasi-experimental investigation: an experimental group and a control group. The experimental group was composed of mothers who participated in 8 virtual coaching appointments, while the control group received only an introductory session. The intervention was preceded and followed by the collection of data through online questionnaires.Coaching was found to be an effective tool for empowering mothers and facilitating their return to society and the labor market, as evidenced by the reduction of limiting beliefs and the increase in the participation of mothers in social activities and entrepreneurship. These findings are consistent with previous research on coaching and the transformation of negative mental patterns. Coaching assisted mothers in playing an active role in society by changing limiting beliefs and strengthening self-efficacy.